The impact of education enrolment and expenditure on economics growth in Thailand - Phua, Jia Yong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The purpose of this study is to examine the impact of education enrolment and expenditure on economics growth in Thailand. The data used in this study was yearly data of 40 years from 1974 to 2013. All data was obtained from the World Bank and United Nations Educational, Scientific, and Cultural Organization (UNESCO) Institute for Statistics. The findings of this study show that there is no long run relationship between education enrolment and expenditure as well as the economic growth in Thailand. However, enrolment in secondary and tertiary education affect the economic growth in Thailand in short run. Moreover, this study also found that education expenditure do not affect the economic growth in Thailand either in short or long run.